COMBATING ORGANIZED CORRUPTION CRIME IN THE SECTOR OF SECURITY AND DEFENSE OF UKRAINE: SYSTEMATIC CHANGES TO THE LEGAL PRINCIPLES (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the determination of ways to improve the legal framework for combating organized corruption crime in the security and defense sector of Ukraine. Arguments are given in favor of the need to adopt the basic law "On the principles of state policy in the field of combating crime". It should define system goals, principled approaches, principles of criminal preventive activities, management in the field of combating crime. In addition to it, the Law of Ukraine "On criminological examination of normative legal acts and their drafts" should be adopted. It is proved that draft laws of Ukraine and other legal acts regulating relations in the security and defense sector should be subject to mandatory criminological examination. It was found out that the specifications require a rule on functional barriers to the privatization of objects of the defense-industrial complex by persons who can be considered oligarchs.
Keywords: crime; organized crime; corruption; security sector and harrows; national security; crime prevention; criminological examination; oligarch; law